2017
DOI: 10.1007/s00253-017-8633-6
|View full text |Cite
|
Sign up to set email alerts
|

Pool deconvolution approach for high-throughput gene mining from Bacillus thuringiensis

Abstract: Novel genes from Bacillus thuringiensis (Bt) are required for effective deployment in agriculture, human health, and forestry. In an improvement over conventional PCR-based screening, next generation sequencing (NGS) has been used for identification of new genes of potential interest from Bt strains, but cost becomes a constraint when several isolates are to be sequenced. We demonstrate the potential of a DNA pooling strategy known as pool deconvolution to identify commercially important toxin genes from 36 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Bacillus thuringiensis ( Bt ) is a Gram-positive soil bacterium expressing insecticidal crystalline proteins (ICPs) that are exceptionally toxic to specific classes of pests ( Panwar et al, 2018 ). Insecticidal activity in insect-resistant Bt crops is expressed by the genes coding for parasporal crystal protoxins ( Palma et al, 2014 ).…”
Section: Biotechnological Approaches In Insect Pest Managementmentioning
confidence: 99%
“…Bacillus thuringiensis ( Bt ) is a Gram-positive soil bacterium expressing insecticidal crystalline proteins (ICPs) that are exceptionally toxic to specific classes of pests ( Panwar et al, 2018 ). Insecticidal activity in insect-resistant Bt crops is expressed by the genes coding for parasporal crystal protoxins ( Palma et al, 2014 ).…”
Section: Biotechnological Approaches In Insect Pest Managementmentioning
confidence: 99%
“…48 There exists a large variety of insects which are not considered IPs neither VHDs, 18,22,23,30,41,49 Biopesticides and anti-pest crops have been developed by genetically modifying the crops with Bt genes, resulting in thousands of Bt strains isolated and studied. 4,20,21,[50][51][52][53][54] However, the evolution of resistance of pests to the insecticidal proteins from Bt produced by transgenic crops is drastically reducing the effectiveness of this method. 50,[55][56][57][58][59][60][61] Indeed, in 2005 was reported that 1 out of 13 insect species were vulnerable to transgenic crops, whereas eight years later, 5 out of 13 had developed resistance to Bt modified crops.…”
Section: Mode Of Action Of Bt Crystals On Insect Pestsmentioning
confidence: 99%
“…Despite the success of the application of Bt crystal proteins for the biological control of pests, at present it is still necessary to identify new Cry toxins with greater toxicity; this approach is considered one of the best ways to counter the potential resistance evolved by insects as well as in developing products against a wider spectrum of insect pests. Traditionally, Bt isolates were screened for their insecticidal spectrum by the time-consuming and laborious insect bioassays [22,46]. Since only a limited number of cry genes have been used for insect control either in sprays or transgenic crops so far, novel insecticidal genes are required [31].…”
Section: New Cry Toxinsmentioning
confidence: 99%
“…The emergence of resistant insects is a problem that both Bt sprays and plant products are likely to face in the future [32]. Several strategies, such as the use of spatial or temporal refugia, high or ultrahigh doses, and gene pyramiding to express two toxins, or two insect control approaches, such that the possibility of evolution of resistance to two toxins/approaches, independent of each other, is greatly diminished, can be a promising approach to prolong the efficacy of products based on Bt [36,46].…”
Section: Resistance To Bacillus Thuringiensismentioning
confidence: 99%